Explaining the Role of Proximate Determinants on Fertility Decline among Poor and Non-Poor in Asian Countries - Majumder, Nabanita (PLoS One, 2015)
OBJECTIVES: We examined the overall contributions of the poor and non-poor in fertility decline across the Asian countries. Further, we analyzed the direct and indirect factors that determine the reproductive behaviour of two distinct population sub-groups. DESIGN: Data from several new rounds of DHS surveys are available over the past few years. The DHS provides cross-nationally comparable and useful data on fertility, family planning, maternal and child health along with the other information. Six selected Asian countries namely: Bangladesh, India, Indonesia, Nepal, Philippines, and Vietnam are considered for the purpose of the study. Three rounds of DHS surveys for each country (except Vietnam) are considered in the present study. METHODS: Economic status is measured by computing a “wealth index”, i.e. a composite indicator constructed by aggregating data on asset ownership and housing characteristics using principal components analysis (PCA). Computed household wealth index has been broken into three equal parts (33.3 percent each) and the lowest and the highest 33.3 percent is considered as poor and non-poor respectively. The Bongaarts model was employed to quantify the contribution of each of the proximate determinants of fertility among poor and non-poor women. RESULTS: Fertility reduction across all population subgroups is now an established fact despite the diversity in the level of socio-economic development in Asian countries. It is clear from the analysis that fertility has declined irrespective of economic status at varying degrees within and across the countries which can be attributed to the increasing level of contraceptive use especially among poor women. Over the period of time changing marriage pattern and induced abortion are playing an important role in reducing fertility among poor women. CONCLUSIONS: Fertility decline among majority of the poor women across the Asian countries is accompanied by high prevalence of contraceptive use followed by changing marriage pattern and induced abortion.